(3GdESWQfhejGs
(3ChdgG (B:s
(3GYde CjgG GdCN GdHGQ GdQMje Cf Yde GdfLhe jfbSe KdGKI CfhGY s
(3BNQgG (B:s
(3JeJ GdQSGdI GdedbHI HGdCSWQfhejG hgj GdeONd Edi Yde GdfLhe ef QSGFd ENhGf GdUaG s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1642s
(3eUOQ GbJfGA GdCUd (B:s
(3GdaGJjcGf (B(494) s
Keywords: (3Gdadcs